1981
DOI: 10.1016/0021-9517(81)90018-x
|View full text |Cite
|
Sign up to set email alerts
|

The hydrogenation of carbon monoxide over rhodium oxide surfaces

Abstract: This is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Rh 0 , is the active sites for CO dissociation, while partially oxidized Rh, i.e. Rh + , is more favorable active sites for CO insertion to form intermediates of C 2 -oxygenates [9][10][11]. As discussed above, the support pretreatment with nC 1 -C 5 alcohols increased the Rh dispersion and the ratio of Rh + / Rh 0 sites, thereby increasing the number of active sites, especially the active sites for CO insertion.…”
Section: The Chemical State Of Rhodiummentioning
confidence: 89%
“…Rh 0 , is the active sites for CO dissociation, while partially oxidized Rh, i.e. Rh + , is more favorable active sites for CO insertion to form intermediates of C 2 -oxygenates [9][10][11]. As discussed above, the support pretreatment with nC 1 -C 5 alcohols increased the Rh dispersion and the ratio of Rh + / Rh 0 sites, thereby increasing the number of active sites, especially the active sites for CO insertion.…”
Section: The Chemical State Of Rhodiummentioning
confidence: 89%
“…Thus, while nickel on alumina is a methanation-only catalyst, on titania it was found to give alkanes and less methane. Watson and Somorjai showed that less methane and more C C2 hydrocarbons were formed on oxidised rhodium catalysts than on the clean metal surface [32,33].…”
Section: Electrophilic Methylidyne Hypothesismentioning
confidence: 99%
“…However, the possibility that Rh + plays a role in CO insertion to form C 2 -oxygenates cannot be ruled out completely. There are reports (18,19) in which Rh + was considered as active sites for the formation of C 2 -oxygenates. The different results obtained in XPS experiments might be due to different catalyst preparation methods, different composition of the catalysts, and different pretreatment of the catalysts.…”
Section: +mentioning
confidence: 99%